Monoethylene glycol as hydrate inhibitor in offshore natural gas processing : from fundamentals to energy analysis /: from fundamentals to energy analysis. (©2018) - Teixeira, Alexandre Mendonc̜a; Arinelli, Lara de Oliveira; Medeiros, José Luiz de; Araujo, Ofelia de Queiroz Fernandes
No abstract available